The Beginning of a New Era in Leather and Footwear in Uzbekistan - Ruzmatov Botir Shermatovich; Mirzayarov Hayitboy Mamatqul o'gli (Zien Journals, 2022)
A new package of privileges has been announced in the field of leather and footwear. In 2022, the leather industry is being supported. In the neighborhoods, measures are being taken to slaughter livestock and launch small mobile services for skin harvesting
Keywords: Leather and footwear; skin reserves; small-horned livestock skin; economical industrial zones